2010
DOI: 10.3389/neuro.09.005.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of attentional and mnemonic processing in event-based prospective memory

Abstract: Prospective memory (PM), or memory for realizing delayed intentions, was examined with an event-based paradigm while simultaneously measuring neural activity with high-density EEG recordings. Specifically, the neural substrates of monitoring for an event-based cue were examined, as well as those perhaps associated with the cognitive processes supporting detection of cues and fulfillment of intentions. Participants engaged in a baseline lexical decision task (LDT), followed by a LDT with an embedded PM componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 77 publications
5
33
0
Order By: Relevance
“…They showed an increased posterior negativity around 200 ms (N200) for ongoing task events performed concurrently with a PM task, relative to ‘ongoing-only task’ performance. This evidence has been corroborated by other researchers (Czernochowski et al, 2012; Knight et al, 2010). Thus, the first question we address in this study is: can the N200 also be found when monitoring conceptual PM cues or is it specific to the monitoring of perceptual PM cues?…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…They showed an increased posterior negativity around 200 ms (N200) for ongoing task events performed concurrently with a PM task, relative to ‘ongoing-only task’ performance. This evidence has been corroborated by other researchers (Czernochowski et al, 2012; Knight et al, 2010). Thus, the first question we address in this study is: can the N200 also be found when monitoring conceptual PM cues or is it specific to the monitoring of perceptual PM cues?…”
Section: Introductionsupporting
confidence: 88%
“…These findings have been replicated for perceptual PM paradigms only (Cousens et al, 2015; Knight et al, 2010; West, 2011). In the comparison of perceptual versus conceptual PM tasks, Cousens et al (2015) observed that only the perceptual task condition elicited the N300, concluding that this modulation may correspond to a specific rather than a general marker of perceptual cue detection.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Interestingly, Cohen et al (2008) analysed word and nonword lexical decision task trials separately and showed more task interference on ongoing LDT word trials relative to nonword trials when participants had a word PM target. Many studies of prospective memory use lexical decision making as the ongoing task and words as PM targets however most of these studies analyse ongoing task performance solely in terms of performance on word LDT trials (for exceptions see Knight, Ethridge, Marsh, & Clementz, 2010;Scullin, McDaniel, Shelton, & Lee, 2010).…”
Section: The Current Studymentioning
confidence: 98%
“…• Test for evaluation of prospective memory -qualitative description (Knight et al, 2010;Staniloiu and Markowitsch, 2012).…”
Section: • Standardized Tests For the Evaluation Of Constructional Fumentioning
confidence: 99%